2007
DOI: 10.1111/j.1365-2265.2007.02807.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mosaicism mitigates stigmata and cardiovascular risk factors in Turner syndrome

Abstract: Mosaicism seems to mitigate the TS phenotype and the cardiovascular risk factor profile. Mosaics were diagnosed 8 years later than 45,X cases. This emphasizes the necessity for a stricter genotype categorization not only in the clinic but also in research on TS than previously adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
87
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 36 publications
12
87
2
4
Order By: Relevance
“…The reduced chance of finding a partner indicates that the awareness of the TS diagnosis to some degree may influence the TS persons' expectations or self-esteem. It also indicates that the phenotype of the TS persons diagnosed late is not as affected as those diagnosed early, as shown previously in a Swedish cohort (12). Nevertheless, we assume that a puberty as similar to peers as possible in onset and timing is important for the individual TS person, in line with previous findings of an increased quality of life in those with spontaneous pubertal timing (13).…”
Section: Discussionsupporting
confidence: 77%
“…The reduced chance of finding a partner indicates that the awareness of the TS diagnosis to some degree may influence the TS persons' expectations or self-esteem. It also indicates that the phenotype of the TS persons diagnosed late is not as affected as those diagnosed early, as shown previously in a Swedish cohort (12). Nevertheless, we assume that a puberty as similar to peers as possible in onset and timing is important for the individual TS person, in line with previous findings of an increased quality of life in those with spontaneous pubertal timing (13).…”
Section: Discussionsupporting
confidence: 77%
“…However, we failed to prove that there is any influence of karyotype on BMD or bone geometry in TS patients in our previous study (8), which is in agreement with many other studies (2,6,7,36,37). A single study showed a normal lumbar spine BMD T-score in patients with 45,X/46,XX mosaicism compared with a decreased BMD T-score in patients with the classical 45,X karyotype (38). However, bone geometry parameters were not assessed in that study.…”
Section: Discussionsupporting
confidence: 70%
“…The higher age for pregnancy in TS women suggests that some of the women may have been karyotyped when they were investigated for infertility, recurrent miscarriages, or ovarian failure with premature menopause rather than for reasons of external TS stigmata or disease. The high age at diagnosis and few stigmata in TS mosaics is in line with previous observations (6).…”
Section: Discussionsupporting
confidence: 79%